2002
DOI: 10.1016/s0960-9822(02)01334-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Analysis of Rac Activation during Live Neutrophil Chemotaxis

Abstract: The ability of cells to recognize and respond with directed motility to chemoattractant agents is critical to normal physiological function. Neutrophils represent the prototypic chemotactic cell in that they respond to signals initiated through the binding of bacterial peptides and other chemokines to G protein-coupled receptors with speeds of up to 30 microm/min. It has been hypothesized that localized regulation of cytoskeletal dynamics by Rho GTPases is critical to orchestrating cell movement. Using a FRET-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(136 citation statements)
references
References 19 publications
8
127
0
1
Order By: Relevance
“…For example, state I cells exhibit initially low, mostly homogeneous Rac activity, followed by the induction of high Rac activity at a newly formed front when a gradient of rapamycin is applied. This pattern of Rac activity is similar to that seen in neutrophils polarizing to a gradient of f-MetLeu-Phe (47). Additionally, state III cells repolarize when given sufficiently high gradients of rapamycin by forming a new front at the rear and retracting the previous front.…”
Section: Discussionsupporting
confidence: 70%
“…For example, state I cells exhibit initially low, mostly homogeneous Rac activity, followed by the induction of high Rac activity at a newly formed front when a gradient of rapamycin is applied. This pattern of Rac activity is similar to that seen in neutrophils polarizing to a gradient of f-MetLeu-Phe (47). Additionally, state III cells repolarize when given sufficiently high gradients of rapamycin by forming a new front at the rear and retracting the previous front.…”
Section: Discussionsupporting
confidence: 70%
“…It is believed that localized activation/deactivation of Rac is critical for CSF-1-induced motility, because the microinjection of both dominant negative Rac and constitutively active Rac prevented cells from developing the proper polarization required for migration, thereby inhibiting motility (3,26). This view is further supported by the finding of Gardiner et al (16) showing that Rac is periodically activated at the leading edge of neutrophils migrating toward chemokines. Many studies have focused on the positive regulators of Rac, such as phosphatidylinositol 3-kinase and Vav that link CSF-1 stimulation to the localized Rac activation at the cell membrane and to motility (45,54,60).…”
Section: Discussionmentioning
confidence: 91%
“…To specifically inhibit Cdc42 during neutrophil activation, the CRIB domain of WASP, which binds Cdc42 but not Rac (or Rho) (41), was introduced into human neutrophils using Bioporter. We have previously shown that this method successfully delivers fluorescently labeled p21-activated kinase CRIB domain into human neutrophils (31). As shown in Fig.…”
Section: Inhibition Of Endogenous Cdc42mentioning
confidence: 87%
“…The proteins were expressed and purified from E. coli and quantified by BCA protein assay (Pierce). The proteins were delivered into neutrophils as previously described (31). Briefly, Bioporter reagent (Gene Therapy Systems, La Jolla, CA) was reconstituted with chloroform according to the manufacturer's instructions, and 2-3 l was aliquoted into Eppendorf tubes and evaporated overnight.…”
Section: Delivery Of Proteins Into Neutrophils Usingmentioning
confidence: 99%